Assessment of banana chips production at different maturity stages of banana using microwave drying - Siti Amira Farhana Binti Umor (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
Banana chips are commonly known as one of the popular dried snacks preferred by the consumers in Malaysia. Banana chips can be produced either by deep frying the banana in the palm oil, or it can be cooked using microwave drying. However, as far as our knowledge concerns, the proper practices in processing the banana chips in the industry are still lacking. A wholly concept of this study is to improvise the quality of end product of the banana chips production. The aims of this study are to analyze the physical properties, chemical properties and sensory evaluation of banana chips produced from different maturity stages of PisangAwakusing microwave drying.In this study, the technique used to produce the banana chips is the microwave heating where banana chips produced using microwave technique tend to be crispier and non-oily which is more healthy. Besides, from collecting the data and conducting the analyses, the best maturity stage of banana to produce banana chips has been assessed. From the result, it was found that microwave dried banana chips at stage 2 was the most desirable as compared to banana chips at stage 1 and stage 3.